Influencia de los Juegos Tradicionales en el desarrollo de la motricidad gruesa en los niños del primer grado de Educación Primaria Institución Educativa Experimental “Rafael Narváez Cadenillas” Trujillo - 2016 - Garcia Maqui, Candy Jakeline (2017)
The research aimed to verify the effectiveness of traditional games in the development of the gross motor skills of children of the first grade primary education educational institution "Rafael Narváez". Taking into account that traditional games are those that are made without the aid of technologically complex toys, but with the body itself or with resources easily available in nature or household objects._x000D_ The research was applied and the quasi experimental, pretest and posttest design with a control group and an experimental group, whose sample was made up of 24 children. The instrument used was the Coarse Motor Development Test (MBPC), which was applied to the sample before and after applying the intervention workshops. The results were analyzed statistically, being that the application of workshops shows effectiveness by significantly increasing the levels of gross motor development in all dimensions evaluated.